Neighbourhood open space in suburban liveability - Ken Taylor (Landscape Review)
This encyclopaedic work by Nichols and Freestone is the result of extensive thinking, international review and research over several years. As the succinct preface page indicates, neighbourhood open space ranks highly as a key component in suburban liveability assessments. In this context, the book connects the past, present and future of planning specifically for small internal open spaces. It resuscitates the enclosed, almost secretive reserve from history as a distinctive form of local open space whose problems and potentialities are relevant to many other green community spaces. This then opens up wider connections between localism and globalism, the past and the future, and connects to broader global challenges of cohesion, health, food and climate change.